Briefing. Issue 12 (17th March 2021) - Unknown
Abstract : Zoom bombing incidents occur on campus Reports of freedom of speech violations spike during COVID‐19 Berkeley imposes stricter residence guidelines for COVID‐19 Student shot in dorm while playing video games